THE MORAL CONSCIOUSNESS DYNAMICS OF STUDENTS IS THE POSITION IN THE PROCESS OF HIGH EDUCATION - Akramov Mirmukhsin Rustamovich (Scholar Express Journal, 2024)
The development of people’s responsible relation to nature consists of the main content ant subject of ecologic component in moral behavior
Keywords: High education; kindness; development